A new target scattering vector. Issue 7 (23rd February 2021) - Yin, Junjun; Yang, Jian
Abstract: This study proposes a new scattering vector parameterisation method for interpreting the coherent target scattering. This new scattering model, which has the same form as the α/β model, consists of five polarimetric parameters including the normalisation factor. Validation is performed on ALOS‐2/PALSAR data. In comparison with the current vector models, the new coherent scattering vector is superior in distinguishing targets with different physical scattering behaviours.